Adoption, usage and impact of broadband: The perspective of Malaysian accountants - Selamat, Mohamad Hisyam; Abd Wahab, Muhammad Syahir; Mat Samsudin, Mohd Amir (Universiti Utara Malaysia, 2008)
The aims of this study are to examine the factors affecting the adoption, the usage and impacts of broadband amongst Malaysian accountants.The data is collected using a survey approach.The findings of this study suggest that attitudinal and control constructs are significant factors in explaining Malaysian accountants’ behavioural intentions to adopt broadband Internet.In term of usage, narrowband and broadband users are significantly different in 19 out of 41 online services.On the impacts of broadband, this research suggests that adopters’ time allocation patterns differ to non-adopters for all 20 daily life activities. However, the differences are found to be significant only for one activity which is spending time with friends.